Sensitivity of daily reference evapotranspiration to weather variables in tropical savanna: a modelling framework based on neural network - Sanjeev Gupta; Pravendra Kumar; Gottam Kishore; Rawshan Ali; Nadhir Al-Ansari; Dinesh Kumar Vishwakarma; Alban Kuriqi; Quoc Bao Pham; Ozgur Kisi; Salim Heddam; Mohamed A. Mattar (Applied Water Science, 2024)
Abstract Accurate prediction of reference evapotranspiration (ETo) is crucial for many water-related fields, including crop modelling, hydrologic simulations, irrigation scheduling and sustainable water management. This study compares the performance of different soft computing models such as artificial neural network (ANN), wavelet-coupled ANN (WANN), adaptive neuro-fuzzy inference systems (ANFIS) and multiple nonlinear regression (MNLR) for predicting ETo. The Gamma test technique was adopted to select the suitable input combination of meteorological variables. The performance of the models was quantitatively and qualitatively evaluated using several statistical criteria. The study showed that the ANN-10 model performed superior to the ANFIS-06, WANN-11 and MNLR models. The proposed ANN-10 model was more appropriate and efficient than the ANFIS-06, WANN-11 and MNLR models for predicting daily ETo. Solar radiation was found to be the most sensitive input variable. In contrast, actual vapour pressure was the least sensitive parameter based on sensitivity analysis.